A Survey of the Status of Supply Substitutability in U.S. Supreme Court and U.S. Circuit Courts of Appeal Cases - GRECO, Anthony J. (Journal of Advanced Research in Law and Economics; Vol 4 No 2 (2013): JARLE Volume IV Issue 2(8) Winter 2013, 2016)
An ongoing problem in the application of U.S. antitrust law is the delineation of the appropriate product market. Demand and supply substitutability, as measured by the coefficients of cross elasticity of demand and the coefficient of elasticity of supply, respectively, were introduced in the early 1950s as two possible criteria to define product markets. Although the implementation and calculation of both concepts involve similar problems, the courts have been more readily receptive of cross elasticity of demand as a criterion on which to define product markets. Since the author has addressed this issue in a recent work, he confines his attention in the present paper to reviewing and updating the use of the supply substitutability concept as a criterion for product market delineation in U.S. Supreme Court and in the Federal Appeals Courts.
Keywords: supply, substitutability, courts